Casa da dança: um espaço sustentável dedicado a dança - Moreira, Mariana Fernandes (2016)
This work has as main objective to study a project of dance center developed to be located in the city of Juazeiro do Norte, in the Northeast. It brings an elaborate study of how to construct spaces for dance in a conscious way, being well located in the city that is situated. A center to support the entire Northeast region, which serves as a school, but also has the teacher, giving support to the dancer in all forms. Outside the capital city, to estimulate the development of the interior city. The project established a good conection with the local patrimony, with the demonstration of a plan to value it and giving it use. The center is divided into three distinct programs: The theater, thought to the whole dance environment and supplying the demand of the Barbalha region; Accommodation, to those who comes from outside the city; And a dance school, which has built a program and an ideal model room for the dance activity. Sustainability applied through adequate strategies for the establishment of passive thermal comfort in the countryside, mainly the analysis and application of the materials. It has also been proposed a generation of sustainable energy, using solar panels on the location where the greatest insolation of the building during the whole year has. In the end, the details of the project were better exposed, explaining some choices and supporting some studies. Finally, we arrive at the final result having a project for a sustainable dance center, the house of the dance.